2020
DOI: 10.1002/jbm.a.36927
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with bisphosphonates to mitigate calcification of elastin‐containing bioprosthetic materials

Abstract: This study evaluated the ability of bisphosphonates (BPAs) of different molecular structures to mitigate the calcification of porcine aortic wall (PAW) and bovine jugular vein wall (BJVW). Tissues cross-linked with glutaraldehyde (GA) or diepoxide (DE) were modified with pamidronic acid (PAM), alendronic acid (ALE), neridronic acid (NER) (type 1 BPAs); 2-(2 0 -carboxyethylamino)ethylidene-1,1-bisphosphonic acid (CEABA), 2-(5-carboxypentylamino)ethylidene-1,1-bisphosphonic acid (CPABA) (type 2); and zoledronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 33 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…12 We previously showed that cross-linking with diepoxide (ethylene glycol diglycidyl ether, DE) significantly reduced the calcification of the BJV wall (BJVW) in a subcutaneous rat model. 20,21 Epoxy treatment has been proven to reduce inflammatory responses, immunogenicity, and cytotoxicity of other bioprosthetic materials. [22][23][24] With this, as well as the excellent results obtained in previous experimental studies, [1][2][3][4] allow us to consider it expedient to develop cross-linking methods using epoxy compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We previously showed that cross-linking with diepoxide (ethylene glycol diglycidyl ether, DE) significantly reduced the calcification of the BJV wall (BJVW) in a subcutaneous rat model. 20,21 Epoxy treatment has been proven to reduce inflammatory responses, immunogenicity, and cytotoxicity of other bioprosthetic materials. [22][23][24] With this, as well as the excellent results obtained in previous experimental studies, [1][2][3][4] allow us to consider it expedient to develop cross-linking methods using epoxy compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that cross‐linking with diepoxide (ethylene glycol diglycidyl ether, DE) significantly reduced the calcification of the BJV wall (BJVW) in a subcutaneous rat model 20,21 . Epoxy treatment has been proven to reduce inflammatory responses, immunogenicity, and cytotoxicity of other bioprosthetic materials 22‐24 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, R2 may contain primary or secondary amines. This group can be used for BP immobilization by binding with an epoxy or aldehyde masking group that remains free after cross-linking of the biomaterial [ 15 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that it involves direct physicochemical effects in inhibiting calcium phosphate nucleation and crystallization. Using elastin-rich biomaterials implanted subcutaneously in rats, we previously demonstrated that the effectiveness of immobilized N-BPs depends on the composition of the extracellular matrix (ECM), the cross-linker used, and the chemical structure of the immobilized compound, rather than on the amount of immobilized BP [ 19 ]. In a screening of six N-BPs, we found that PAM and 2-(2′-carboxyethylamino)ethylidene-1,1-bisphosphonic acid (CEABA) ( Figure 1 ) had the strongest inhibitory effect on the calcium-binding capacity of porcine aortic (Ao) and bovine jugular vein (Ve) walls, cross-linked with GA or ethylene glycol diglycidyl ether (DE) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation